Cattle grazing reduces fuel and leads to more manageable fire behavior - Felix Ratcliff; Devii Rao; Sheila Barry; Shane Dewees; Luke Macaulay; Royce Larsen; Matthew Shapero; Rowan Peterson; Max Moritz; Larry Forero (California Agriculture, 2022)
Cattle play an important role in wildfire management by grazing fuel on California rangelands. The benefits of cattle grazing have not been thoroughly explored, though. Using statewide cattle inventory, brand inspection and land use data, we have estimated that cattle removed 11.6 billion pounds (5.3 billion kilograms [kg]) of non-woody plant material from California's rangelands in 2017. Regionally, these reductions varied between 174 and 1,020 pounds per grazed acre (195 to 1,143 kg per hectare). Fire behavior is characterized in this paper by flame length. Fire behavior models suggest that these regional fuel reductions lower flame lengths, and lead to more manageable wildfires. In addition, fire-based models show that cattle grazing reduces fuel loads enough to lessen fire hazards in many grazed areas. Moving forward, there may be significant opportunities to expand strategic grazing on rangelands to add extra layers of protection against wildfires.